TEC variations during geomagnetic storm/substorm with Pc5/PI2 pulsation signature. Issue 11 (1st June 2015) - Hamada, A.M.; Mahrous, A.M.; Fathy, I.; Ghamry, E.; Groves, K.; Yumoto, K.
Abstract The electron density integral along the paths between a GPS satellite and receiver is known as Total Electron Content (TEC), and this parameter is used in studying the ionosphere behaviors. TEC can be obtained by means of many methods. A space-based radio navigation system, such as Global Positioning System (GPS), offers good opportunities for studying the ionosphere. The TEC is calculated from the group path delay and phase advance in GPS satellite signals along the slant paths connecting GPS receivers and satellites at 22, 000 km. Locally, a dual frequency GPS receiver was installed in Helwan, Egypt (29.86°N, 31.32°E) in November 2009. Here, GPS data were analyzed to establish a daily observation of Vertical TEC in a region located near to the northern crest of the ionospheric equatorial anomaly. During a moderate geomagnetic storm, observed on 02–05 May 2010, a number of ionospheric/magnetic phenomena were observed. Also, observations for Pc5/Pi2 pulsations were recorded during the geomagnetic storm phases. These geomagnetic observations are taken from MAGDAS-magnetometer station, located at Aswan (23.59°N, 32.51°E). More than 10 TECU increase in the ionospheric TEC values were recorded during the daytime of 02 May, followed by a large reduction during 03 May, reference to the pre-storm conditions. This confirms the enhancement in the geomagnetic H-component peak during the storm's initial phase and its reduction during the main phase.